Polymorphisms in salivary-gland transcripts of Russian wheat aphid biotypes 1 and 2 - Cui, Feng; Smith, C. Michael; Reese, John C.; Edwards, Owain; Reeck, Gerald R. (My University, 2012)
The Russian wheat aphid (RWA), Diuraphis noxia (Mordvilko) (Homoptera: Aphididae), is a major pest of small grains. As with plant-feeding aphids in general, the interaction between RWA and host plants is governed, on the insect side, by proteins and enzymes in saliva. In this work, we examined sequence variations in transcripts encoding proteins and enzymes of RWA salivary glands. We conducted reverse transcription – polymerase chain reaction in RWA biotypes 1 and 2 using primers derived from pea aphid orthologs, and cloned regions of 17 putative salivary gland transcripts. For four of the transcripts, we observed no difference in sequences between the two biotypes. For the other 13 transcripts, for example, the transcripts encoding sucrase, trehalase and protein C002, large amount of variations, both within each biotype and between the two biotypes, were observed. Usually the two biotypes shared only one variant, which was typically the most common variant in both biotypes. Most of the transcripts had more non-synonymous than synonymous codon changes among their variants. Our results offer possible molecular markers for distinguishing the two biotypes and insights into their evolution.
Citation: Cui, F., Smith, C. M., Reese, J., Edwards, O., & Reeck, G. (2012). Polymorphisms in salivary-gland transcripts of Russian wheat aphid biotypes 1 and 2. Retrieved from http://krex.ksu.edu
Keywords: Biotype; Molecular marker; Polymorphism; Russian wheat aphid; Salivary gland; Transcript